2012
DOI: 10.1128/ec.05262-11
|View full text |Cite
|
Sign up to set email alerts
|

The Giardia Median Body Protein Is a Ventral Disc Protein That Is Critical for Maintaining a Domed Disc Conformation during Attachment

Abstract: Giardia has unique microtubule structures, including the ventral disc, the primary organelle of attachment to the host, and the median body, a structure of undefined function. During attachment, the ventral disc has a domed conformation and enables Giardia to attach to the host intestinal epithelia within seconds. The mechanism of attachment via the ventral disc and the overall structure, function, and assembly of the ventral disc are not well understood. Our recent proteomic analysis of the ventral disc indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 36 publications
7
80
0
Order By: Relevance
“…Here we employed ns-ET to gain a large-field overview of a complete Giardia ventral disc by montaging 4 × 4 tomograms into one continuous volume of which a ~180 nm thick xy-slice is shown in figure 2A. The overall orientation of the disc in figure 2A is the same as in 2B, a 3View® reconstruction (Gatan Inc. Pleasanton CA; Denk & Horstmann, 2004; see also Schwartz et al, 2012) where the ventral disc is shown in pink, with the two nuclei in cyan, the median body in brown (Woessner & Dawson, 2012), and the four pairs of flagella in green (anterior), blue (caudal), yellow (ventral), and red (post-lateral; Dawson & House, 2010B). The flagellar basal bodies are clearly visible in the tomographic reconstructions of the disc preparations (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we employed ns-ET to gain a large-field overview of a complete Giardia ventral disc by montaging 4 × 4 tomograms into one continuous volume of which a ~180 nm thick xy-slice is shown in figure 2A. The overall orientation of the disc in figure 2A is the same as in 2B, a 3View® reconstruction (Gatan Inc. Pleasanton CA; Denk & Horstmann, 2004; see also Schwartz et al, 2012) where the ventral disc is shown in pink, with the two nuclei in cyan, the median body in brown (Woessner & Dawson, 2012), and the four pairs of flagella in green (anterior), blue (caudal), yellow (ventral), and red (post-lateral; Dawson & House, 2010B). The flagellar basal bodies are clearly visible in the tomographic reconstructions of the disc preparations (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…B: 3-D reconstructions of Giardia lamblia from Schwartz et al (2012) by a procedure called 3View (Denk & Horstmann, 2004). This SEM and microtomy 3-D reconstruction approach reveals the overall architecture of the Giardia cell with the ventral disc (pink) the nuclei (cyan), the median body (brown; Woessner & Dawson, 2012), and the four flagellar pairs in green (anterior), blue (caudal), yellow (ventral) and red (post-lateral; Dawson & House, 2010B). …”
Section: Figurementioning
confidence: 99%
“…The unregulated maintenance of episomes might lead to elevated and uneven expression levels, as noticed previously in G. intestinalis transfectants (32). We utilized singlecrossover homologous recombination, previously shown to be effective in G. intestinalis (10,14,34), for the construction of a chromosomally integrated BiP-2ϫOLLAS strain (see Fig. S3 in the supplemental material).…”
Section: Discussionmentioning
confidence: 98%
“…Although still poorly understood, it is clear that the attachment of the parasite to the mucosal surface is the critical point for its persistence in the host. The parasite contains a ventral disk that seems to be important for attachment (Woessner and Dawson, 2012), while the flagella contributes to correct positioning and orientation of the trophozoites before the attachment (House et al, 2011). The parasite actively engages mucosal immunity and the infection progresses with a low or absent inflammation in most cases (Oberhuber and Stolte, 1997).…”
Section: Introductionmentioning
confidence: 99%